(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The influence of rapid thermal annealing on the electrical and structural properties of Au/Cr/n-InP Schottky diode havebeen investigated by the current-voltage (I-V), capacitance-voltage (C-V), auger electron spectroscopy (AES) and X-ray diffraction (XRD) measurements. The Schottky barrier height (SBH) and ideality factor (n) of the as-deposited Au/Cr/n-InPSchottky diode are 0.51 eV (I-V)/0.64 eV (C-V) and 1.81, respectively. When the contact is annealed at 200 oC in N2 atmosphere for 1min, a maximum SBH (0.71 eV (I-V)/0.81 eV (C-V)) and low ideality factor (1.15) are achieved for theAu/Cr/n-InP Schottky diode. However, after annealing at 300 oC, the SBH slightly decreases to 0.58 eV (I-V)/0.69 eV (CV), and ideality factor increases to 1.45, respectively. The SBHs obtained from the Norde and Cheungs methods areclosely matched with those obtained from the I-V method. Results show that the optimum annealing temperature for theAu/Cr/n-InP Schottky diode is 200 °C. Further, the discrepancy between SBHs calculated from I-V and C-V methods isalso discussed. Moreover, the energy distribution of interface state density is estimated from forward bias I V characteristics at different annealing temperatures. AES and XRD studies reveal that the formation of indium (In) phasesat Au/Cr and InP interface may be the cause for the increase in SBH after annealing at 200 oC. The AFM results show that the overall surface morphology of Au/Cr Schottky contacts is considerably smooth at elevated tempratures.